2023
DOI: 10.3390/pharmaceutics15061708
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Hyaluronan-Based Thermoresponsive Hydrogels for Dermatological Applications

Abstract: Most marketed HA-based dermal fillers use chemical cross-linking to improve mechanical properties and extend their lifetime in vivo; however, stiffer products with higher elasticity require an increased extrusion force for injection in clinical practice. To balance longevity and injectability, we propose a thermosensitive dermal filler, injectable as a low viscosity fluid that undergoes gelation in situ upon injection. To this end, HA was conjugated via a linker to poly(N-isopropylacrylamide) (pNIPAM), a therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Contrastingly, the remaining fractions of the loss moduli G ′′ were found to be significantly lower for the VOLBELLA ® product as compared to the other tested products (Figure 2B, Table S3). Of note, H 2 O 2 is the most common and simplest ROS generator to be used when evaluating the in vitro oxidative degradation of HA [25]. As previously mentioned, two major mechanisms that contribute to the degradatio of HA-based gels are oxidative reactions and enzymatic catabolism (i.e., primarily vi hyaluronidases).…”
Section: Har Hydrogel Multi-parametric Accelerated Degradation Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrastingly, the remaining fractions of the loss moduli G ′′ were found to be significantly lower for the VOLBELLA ® product as compared to the other tested products (Figure 2B, Table S3). Of note, H 2 O 2 is the most common and simplest ROS generator to be used when evaluating the in vitro oxidative degradation of HA [25]. As previously mentioned, two major mechanisms that contribute to the degradatio of HA-based gels are oxidative reactions and enzymatic catabolism (i.e., primarily vi hyaluronidases).…”
Section: Har Hydrogel Multi-parametric Accelerated Degradation Assaysmentioning
confidence: 99%
“…Additionally, numerous studies evaluated and benchmarked various finished product bio-physical attributes (e.g., extrusion forces, cohesivity, and swelling ratio). Importantly, the hydrogel characterization methodologies were largely consistent across studies, with minimal variations in approaches and results [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. However, experimental unraveling of the degradation mechanisms in cross-linked HA-based fillers is highly complex and challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported the in situ formation of a hydrogel of hyaluronic poly (N-isopropylacrylamide) prepared using click chemistry [46]. Termosensitive hyaluronic acid-based injectable hydrogels were recently reported through the conjugation of hyaluronic acid with poly (N-isopropyl acrylamide), the produced hydrogel exhibited in situ gelation at body temperature, and study results indicate good compatibility with prolonged residence at the injection site which is regarded crucial for e for ensuring the treatment's maximum efcacy [47].…”
Section: Termoresponsive Hyaluronic Acid-based Injectablementioning
confidence: 99%
“…However, paramount remains the imperative of rigorous research and clinical scrutiny to affirm the safety and efficacy of these formulations, setting the stage for evidence-driven practice in this dynamic domain. 13…”
Section: Herbal Nanoformulations For Diverse Dermatological Disordersmentioning
confidence: 99%